Xenomonitoring of sleeping sickness transmission in Campo (Cameroon). Issue 1 (December 2016) - Grébaut, Pascal; Melachio, Trésor; Nyangmang, Simplice; Eyenga, Vincent; Njitchouang, Guy-Roger; Ofon, Elvis; Njiokou, Flobert; Simo, Gustave
Abstract Background The sleeping sickness focus of Campo in South Cameroon is still active, at a low endemic level, for more than a century, despite a regular medical surveillance. The present study focuses on the spatial distribution of xenomonitoring information obtained from an entomological survey performed in the dry season 2012. It appears that humans constitute a third of the blood meals and that the flies' densities were coherent with those classically observed in the different biotopes. Paradoxically, the epicenter of the focus is the place where the risk indicators are the lowest ones. Methods Particular attention was paid to the entomological device so that it covered the main part of human activities in the study area. One hundred and sixty-two pyramidal traps were used to catch tsetse flies twice a day that were identified, counted, dissected. Molecular analysis using classical and specific molecular markers was conducted to determine the importance of trypanosome infections and the nature of the feeding hosts. This information was used to calculate a Transmission Risk Index and to define a gradient of risk that was projected into a Geographical Information System. Results Conventional entomological indicators such as species identification of tsetse flies or the Apparent Density per Trap per day, show thatGlossina palpalis palpalis is the main species in the campo area which is classically distributed into the different biotopes of the study area. Molecular analysis reveals that humans constitute a third of the blood feeding hosts and that 20 % of the dissected flies were infected with trypanosomes, principally withNannomonas . Nevertheless, one fly was carryingTrypanosoma brucei gambiense, the pathogen agent of sleeping sickness, showing that the reservoir is still active in the epicenter of the focus. Paradoxically, the Transmission Risk Index is not important in the epicenter, demonstrating that endemic events are not only depending on the man/vector contact. Conclusion Xenomonitoring provides a valuable guide/tool to determine places at higher risk for vector/human contact and to identify trypanosomes species circulating in the focus. This information from xenomonitoring demonstrates that decision makers should include a veterinary device in a control strategy.